Implementation of Information Gathering Method in Academic Information System (SIAKAD) - Alfiah, Fifit; Setiadi, Ade; Marsela, Marsela; Syahdan, Devina; Natasya, Sadrina (UNIVERSITAS RAHARJA, 2025)
With the rapid development of information technology today, we must continue to follow the development of the digital transformation era, where educational institutions need a strong system to manage information efficiently. Academic Information Systems are an important framework that helps educational organizations simplify their functions, improve communication, improve student services, process student and teacher data in schools, and support decision-making processes. The purpose of creating this system at Avicena Rajeg Vocational School is to facilitate the administrative process, especially data management because previously there was no system to help students and teachers manage data. The authors used information gathering methods to conduct their research. This method collects data from the authorities to find out the root cause of the problem, and then analyzes the data. In order to obtain the data, the authors conducted direct observations in schools, the collection and study of documents—documentation that will help with this research—and interviews with relevant parties in schools are necessary. At this point, some problems were found with the management of school data and solutions to these problems. The results of this research will help in the development of a more efficient academic information system. The result is that with a data management system for teachers and students, everything will be more organized and more informed.